GC‐MS analysis of ethyl carbamate in distilled sugar cane spirits from the northern and southern regions of Minas Gerais. Issue 4 (29th September 2014) - Masson, José; das Graças Cardoso, Maria; Zacaroni, Lidiany Mendonça; dos Anjos, Jeancarlo Pereira; Santiago, Wilder Douglas; Machado, Ana Maria de Resende; Saczk, Adelir Aparecida; Nelson, David Lee
<x xml:space="preserve">Abstract</x> Ethyl carbamate, also known as urethane, is the ethyl ester of carbamic acid. Animal studies with this compound have demonstrated its carcinogenic potential. In this study, gas chromatography coupled to mass spectrometry (GC‐MS) was applied for the determination of ethyl carbamate in sugar cane spirits in the northern and southern regions of the state of Minas Gerais in Brazil. The samples were collected from distillates from small‐ and medium‐scale stills. The concentrations determined for ethyl carbamate in the samples ranged from 23 to 980 µg L−1. All of the samples analysed from the southern region of Minas Gerais had an ethyl carbamate content below the limit set by the Brazilian legislation for ethyl carbamate of 150 µg L−1, while a number of samples from northern Minas Gerais exceeded this limit. No correlations were observed between the levels of ethyl carbamate and the alcohol content, acidity or copper concentrations in the samples. Copyright © 2014 The Institute of Brewing & Distilling